Expanding Role of Contrast-Enhanced Ultrasound and Elastography in the Evaluation of Abdominal Pathologies in Children - Natae Fekadu Lemessa; Laith R. Sultan; Santiago Martinez-Correa; Laura May Davis; Misun Hwang (Diagnostics, 2025)
Contrast-enhanced ultrasound and elastography are two ultrasound technologies that are becoming increasingly popular in the evaluation of different abdominal pathologies in children. The use of these technologies has expanded the diagnostic scope of ultrasound into areas that were traditionally covered by advanced imaging modalities such as computed tomography, magnetic resonance imaging, and fluoroscopy. In this review, we summarize the use of contrast-enhanced ultrasound and elastography in the evaluation of hepatic, renal, pancreatic, splenic, urinary tract, and scrotal pathologies in children. We describe the technical aspects, applications, and limitations, intending to make readers more acquainted with the technologies.